نقص التنسج المينائي المترافق مع نخور الطفولة المبكرة الشديدة عند أطفال اللاذقية ( دراسة إحصائية) - Raslan, Nabih; aljlki, Celine awad (Latakia University Journal -Medical Sciences Series, 2019)
سيلين العوض الجلقي نبيه رسلان نقص التنسج المينائي المترافق مع نخور الطفولة المبكرة الشديدة عند أطفال اللاذقية ( دراسة إحصائية) الهدف: الهدف من هذه الدراسة هو تحديد نسبة انتشار وشدة نقص التنسج المينائي و ترافقة مع نخور الطفولة المبكرة الشديدة لدى الأطفال بعمر (3-1) سنوات, وذلك في مدينة اللاذقية السورية, وتحديد أهم عوامل الخطورة المؤهبة لحدوث نقص التنسج المينائي. المواد والطرق: هذه الدراسة هي دراسة مقطعية ذات عينة مؤلفة من 521 طفلاً تتراوح أعمارهم بين (3-1) سنوات, تم تنظيف أسنانهم قبل الفحص باستخدام اللفافات القطنية وأجري الفحص في ضوء النهار وذلك في المراكز الصحية خلال حملات اللقاح الوطنية, وسجلت درجات نقص التنسج و النخر في أسنانهم المؤقتة باستخدام دليل Caufeild لعام 2012 وأجري استبيان مع أمهاتهم, وجمعت معلومات تتضمن عوامل الخطورة للإصابة بنقص التنسج في الفترة قبل وبعد الولادة. النتائج : كانت نسبة انتشار نقص التنسج المينائي (EHP) غير المترافق مع آفات نخرية 10,55% ونقص التنسج المترافق مع آفات نخرية 7,1%, وأكثر الأسنان إصابة به كانت القواطع المؤقتة العلوية وأقلها إصابة القواطع السفلية , كما لم يكن هناك فرق بين إصابة الذكور والإناث به (P>0,05), وكانت أهم العوامل المؤهبة لحدوثه هي الأمراض التي أصابت الطفل بعد الولادة وخلال العام الأول من عمره (P>0,05). الاستنتاج :نسبة انتشار نقص التنسج المينائي كانت مرتفعة نسبياً عند أطفال اللاذقية , وقد ترافق وجوده بشكل قوي مع حدوث نخور الطفولة المبكرة. Aim of study : The aim of the present study was to examine the prevalence, severity and association of enamel hypoplasia (EHP) and sever early childhood caries (S-ECC) in a sample of (1-3) years old children living in lattakia , Syria. And identify the most important risk factors for the occurrence of enamel hypoplasia. Materials and Methods: A cross – sectional study was carried out with 521 children aged 1-3 years. The teeth were cleaned with cotton swabs and examined in the open air, avoding direct sunlight . Data were collected through clinical examinations and interviews with mothers during National Immunisation Days . The diagnosis of enamel hypoplasia and caries was performed using Caufeild Index 2012 . Data collected were : Risk factor before and after natal. Results: The prevalence of Enamel hypoplasia (EHP) was 10,55% (without early childhood caries) and EHP associated with early childhood caries was 7,1% . The teeth most affected were maxillary incisors, while the least affected teeth were mandibular incisore . There was no difference in the prevalence of EHP between boys and girls (p>0.05), and the most important risk factors were the diseases that affected the child at brith and in the first year of his life (P>0,05). Conclusion: The precence of enamel hypoplasia was relatively high at lattakia children and association with dental caries.